A DC-DC converter based on the three-state switching cell for high current and voltage step-down applications - Balestero, Juan Paulo Robles; Tofoli, Fernando Lessa; Torrico-Bascopé, Grover Victor; Seixas, Falcondes José Mendes de (Institute of Electrical and Electronics Engineers (IEEE), 2013)
This paper presents a pulsewidth modulation dc-dc nonisolated buck converter using the three-state switching cell, constituted by two active switches, two diodes, and two coupled inductors. Only part of the load power is processed by the active switches, reducing the peak current through the switches to half of the load current, as higher power levels can then be achieved by the proposed topology. The volume of reactive elements, i.e., inductors and capacitors, is also decreased since the ripple frequency of the output voltage is twice the switching frequency. Due to the intrinsic characteristics of the topology, total losses are distributed among all semiconductors. Another advantage of this converter is the reduced region for discontinuous conduction mode when compared to the conventional buck converter or, in other words, the operation range in continuous conduction mode is increased, as demonstrated by the static gain plot. The theoretical approach is detailed through qualitative and quantitative analyses by the application of the three-state switching cell to the buck converter operating in nonoverlapping mode $(D < 0.5)$. Besides, the mathematical analysis and development of an experimental prototype rated at 1 kW are carried out. The main experimental results are presented and adequately discussed to clearly identify its claimed advantages. © 1986-2012 IEEE.
Keywords: Buck converter; dc-dc converters; three-state switching cell (3SSC); Active switches; Buck converters; Continuous conduction mode; Coupled inductor; Discontinuous conduction mode; Experimental prototype; High currents; Intrinsic characteristics; Load currents; Load power; Mathematical analysis; Nonisolated; Nonoverlapping; Operation range; Output voltages; Peak currents; Power levels; Qualitative and quantitative analysis; Reactive elements; Ripple frequency; Theoretical approach; Total loss; Cells; Cytology; Switching; Topology; DC-DC converters